Dimensions of user participation in non-profit mobile crowdsourcing initiatives - Mahmud F.; Aris H. (Universiti Putra Malaysia Press, 2023)
Mobile devices have seemingly become a necessity in peoples daily life. They have significantly changed the way people communicate and perform their day-to-day activities. In line with this scenario, there is a practice nowadays that is gaining more and more attention from mobile application developers called crowdsourcing. The combination of the two innovations, i.e. mobile devices and crowdsourcing, promises great potential for the advancement of business and society. Despite the popularity of mobile crowdsourcing applications, special attention needs to be given to user participation, since user participation is one of the main factors that determine the success of a mobile crowdsourcing application. This study, therefore, aims at identifying the factors that influence user participation in mobile crowdsourcing application. The interview method involving 13 mobile crowdsourcing application users was used to collect the required information. The constant comparison method comprising open coding, axial coding and selective coding techniques was used to analyse the results. Findings from the analysis showed that user participation in mobile crowdsourcing applications is mainly influenced by the personal benefits that the applications can bring to the user rather than the benefit it can bring to others. These benefits cover five dimensions: financial impact, useful information provided, interaction with other users, rewards offered and features of the applications. 2017 Universiti Putra Malaysia Press.